2003
DOI: 10.1093/ps/82.8.1223
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of aging on fitness and nonfitness traits in laying hens housed three per cage

Abstract: Three White Leghorn strains, their two-way crosses, and two commercial lines were used to study the effects of aging on several parameters related to performance of fitness and nonfitness traits during the first laying cycle of hens housed three per cage. Egg number of the survivors (EPF) and egg number including mortality and morbidity (EPM) were divided into 12 periods of 28 d each, starting at age at sexual maturity. Egg weight (EW), specific gravity (SG), and albumen height (AH) were measured at 240, 350, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Relatively, the magnitude of heritability estimates of most increment traits for 20-and 30-wk intervals were moderate. This increasing trend may indicate that additive genetic variance increased with age for egg weight (Ledur et al, 2003;Niknafs et al, 2012). Two previous studies reported that egg weight increments from 210 to 310 d were much more affected by environmental factors (Poggenpoel and Duckitt, 1988;Shalev and Pasternak, 1993), implying a larger contribution of environmental variance, similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…Relatively, the magnitude of heritability estimates of most increment traits for 20-and 30-wk intervals were moderate. This increasing trend may indicate that additive genetic variance increased with age for egg weight (Ledur et al, 2003;Niknafs et al, 2012). Two previous studies reported that egg weight increments from 210 to 310 d were much more affected by environmental factors (Poggenpoel and Duckitt, 1988;Shalev and Pasternak, 1993), implying a larger contribution of environmental variance, similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…The direct additive effects model without any maternal effects was suitable for egg production (Ghorbani et al., 2012; Le Bihan‐Duval et al., 1998; Norris & Ngambi, 2006), which was true in the present study also. A comprehensive review of the literature revealed that additive genetic variation increased with age for egg production and egg weight (Engstrom et al., 1992; Ledur et al., 2003; Niknafs et al., 2012). However, some authors reported maternal effects in addition to the direct additive effects for the egg production and egg weight (Jasouri et al., 2017; Misztal & Besbes, 2000; Yousefi et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of egg specific gravity for the genetic improvement of eggshell quality is sometimes controversial, the additive variability of egg specific gravity accounts for ca. 20%-45% of the total trait variability (Nirasawa et al, 1998;Ledur et al, 2003;Begli et al, 2010;Rozempolska-Rucińska et al, 2011), thereby making it a predictor candidate in effective selection for eggshell quality. The objections against the use of egg specific gravity as a trait that defines eggshell quality in a broad sense are mainly related to the fact that the reliability of this measurement largely depends on environmental factors, e.g., the duration of egg storage or the lag of measurement time (Voisey and Hamilton, 1977;Sloan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%